Spiritual being in Parmalim theology of the Batak people in North Sumatra - Sirait, Sangkot (HTS teologiese studies, 2024)
This article explains the religious system of Parmalim sect found in the Batak lands of North Sumatra. The problem in the research is how the Parmalim theology is constructed and several aspects related to the religious ceremonies. In Parmalim, theology and religious rituals tend to be more dominant with natural theology. The main teachings of this sect mostly come from narratives and cultural texts and ethical teachings of the Batak community. This community still exists today because of its ability to adapt to the culture of the community and the support of the traditional Batak leaders themselves.Contribution: The study provides vital insights into the religious composition of the Parmalim sect and the socio-cultural factors contributing to its resilience. It contributes to the broader understanding of religious diversity, tolerance and the role of leadership in the survival of such communities, aligning with the journal’s focus on religious studies and cultural dynamics.